Local Wisdom as a Foundation for Best Practices in Building Places of Worship: A Study of the Anduonohu Station Catholic Church in Kendari City - Saputra, Muhammad Ali (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
Although Indonesia’s Constitution guarantees the freedom to build places of worship, particularly for religious minorities, the process still encounters many obstacles. To address administrative issues, the government issued Joint Ministerial Regulations (PBM) No. 9 and 8 of 2006. However, these regulations often fail to resolve conflicts surrounding church construction.This study explores local wisdom as an alternative approach for best practices in building houses of worship in Kendari City. Taking the peaceful construction of the Anduonohu Stasi Catholic Church as a case study, the research reveals that the project succeeded without resistance from the predominantly Muslim local community. The church fully met all administrative requirements under existing regulations. Although not explicitly framed as local wisdom, the construction was supported by strong values of responsibility, mutual respect, love, and willingness to sacrifice—demonstrated by residents, the church, and other stakeholders. While neighbors did not provide financial or physical help, they willingly accepted the presence of the church by choosing not to oppose it. The government contributed through permits, recommendations, and assistance. Due to time constraints in data collection, further research is needed to deeply explore these best practices and the role of local wisdom in fostering religious tolerance.